Studying Religious Pluralism in Yorubaland: A Tribute to J. D. Y. Peel - Janson, Marloes (Religion and Society, 2017)
Sub-Saharan Africa is frequently, but unjustly, seen as the periphery of the Muslim world, in terms of both geography and religious influence. By contrast, North Africa is considered to be directly linked to the alleged center of the Muslim world, that is, the Arab Middle East. In fact, Islam has had a presence in sub-Saharan Africa since the earliest days of its history. This chapter tries to redress the periphery bias in the analysis of African Muslim societies – a bias that, as Loimeier (2013: ix-x) points out, is long overdue. After all, Africa is home to one of the largest agglomerations of Muslims in the world today.
paid
Keywords: Christianity and African religions; Christianity and Islam – 1900; Islam and African religions; Peel; J D Y; Pluralism; Religious; Yoruba (African people) – Religion